2015
DOI: 10.1038/srep15967
|View full text |Cite
|
Sign up to set email alerts
|

E. adenophorum induces Cell Cycle Arrest and Apoptosis of Splenocytes through the Mitochondrial Pathway and Caspase Activation in Saanen Goats

Abstract: The precise cytotoxicity of E. Adenophorum in relation to the cell cycle and apoptosis of splenocytes in Saanen goats remains unclear. In the present study, 16 Saanen goats were randomly divided into four groups, which were fed on 0%, 40%, 60% and 80% E. adenophorum diets. The results of TUNEL, DAPI and AO/EB staining, flow cytometry analysis and DNA fragmentation assays showed that E. adenophorum induced typical apoptotic features in splenocytes, suppressed splenocyte viability, and caused cell cycle arrest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…Previous studies showed that the ingestion of A. adenophora as a feed additive induced hepatotoxicity in mice 28 and rat 7 , as well as chronic pulmonary disease in horses 29 . In our previous studies, apoptosis pathway was triggered by A. adenophora in goat and mice 10 , 30 , 31 . In this study, IL-1β, a pro-inflammatory cytokine, was induced by A. adenophora (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies showed that the ingestion of A. adenophora as a feed additive induced hepatotoxicity in mice 28 and rat 7 , as well as chronic pulmonary disease in horses 29 . In our previous studies, apoptosis pathway was triggered by A. adenophora in goat and mice 10 , 30 , 31 . In this study, IL-1β, a pro-inflammatory cytokine, was induced by A. adenophora (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…For detection of cell apoptosis, FITC Annexin V Apoptosis Detection Kit I (BD Pharmingen, NJ, USA) was used and performed according to the manufacturer's instruction and more details were according to the previous study [45]. …”
Section: Methodsmentioning
confidence: 99%
“…The pollen grains and volatile metabolites cause respiratory problems in humans, and digestive problems in susceptible animals. Its allelopathic competition with other plants is a major cause of loss to agriculture and native plant diversity (Liao et al 2014;He et al 2015).…”
Section: Degradation Of Euptox Amentioning
confidence: 99%
“…The plant is originally native to Mexico, but at present it has spread in many parts of the world. It contains hepatotoxic 9-oxo-10,11-dehydroageraphorone (also called euptox A) and pyrrolidizine alkaloids that cause pulmonary toxicity (pulmonary interstitial fibrosis, emphysema and alveolar epithelisation) in equine (Oelrichs et al 1995), cell cycle arrest, apoptosis in splenocytes, suppressed splenocyte viability and various health problems (Bhardwaj et al 2001;Liao et al 2014;He et al 2015).…”
Section: Introductionmentioning
confidence: 99%